PREPARATION AND CHARACTERIZATION OF AZILSARTAN COCRYSTALS USING AMINO ACIDS AS COFORMERS - VANGALA LAVANYA; ANNAMMADEVI GS (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: This study aimed to improve the solubility and dissolution of azilsartan by forming cocrystals with D-alanine. Methods: Azilsartan-D-alanine cocrystals were prepared using a 1:2 molar ratio through the solvent evaporation technique. Cocrystal formation was confirmed through Fourier transform infrared spectroscopy (FT-IR), DSC, PXRD, and scanning electron microscope (SEM). In vitro dissolution was evaluated using a USP Type II paddle apparatus with 900 mL of dissolution medium maintained at 37±0.5°C. Results: FT-IR analysis confirmed the presence of hydrogen bonding through significant shifts in the functional group peaks. The DSC analysis exhibited a sharp endothermic peak, signifying the development of a new crystalline phase, whereas PXRD results displayed unique diffraction peaks not observed in the individual drug or coformer, validating the formation of cocrystals. SEM analysis showed a morphological transformation into a homogeneous and compact structure. The cocrystals exhibited enhanced dissolution performance, achieving a 1.35-fold increase in drug release at 60 min compared to pure azilsartan. Conclusion: The study successfully demonstrates that cocrystallization with D-alanine significantly improves the solubility and dissolution of azilsartan. This method provides an effective way to tackle solubility issues while potentially improving the oral bioavailability of drugs with poor water solubility. The study also underscores the value of amino acid-based coformers in pharmaceutical cocrystal development.